Interaksi Pertimbangan Etika Dan Perilaku Penyusun Anggaran Terhadap Senjangan Anggaran Pemerintah Daerah - Helda Marlin Ala; Mesri Welhelmina Nisriani Manafe (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2020)
This study aims to examine the impact of the interaction between budget compilers' behavior and ethical considerations on budgetary slack in the Regional Apparatus Organization (OPD) within the Kupang City Government. The test was carried out using multiple linear regression analysis to test the effect of partial, simultaneous and interaction between variables through a quasi-experimental design. The research results began with the classical assumption test, which showed significant results for all tests. The partial test of the independent variable of budget compiler behavior (X1) and ethical considerations (X2) shows support at the significance level <0.05. Simultaneous test shows the effect at the level of 0.000<0.05, which means that simultaneously the variables X1 and X2 have an effect on variable Y with a R2 value of 41%. The results of the interaction test show that the moderating variable causes the hypothesis 4 to be unsupported at the significance level >0.05. The results of this study are expected to contribute to local governments in the budget planning and implementation process by considering the trends in budgetary slack that may be made by budget compilers with considerations of ethics and internalized norms and behavior when preparing the budget.